Comparison of high efficiency and standard induction motors with different speed control methods - (:unkn) unknown (My University, 2012)
Electric motors convert more than half of all the electrical energy produced in developed countries into mechanical energy. Induction motors (IM) are estimated to make up 90% of electric motors. Efficiency improvements to these motors can produce major cost savings. High-efficiency motors, which limit losses in electric motors, can be given more efficient energy consumption and performance through the use of speed control drivers. Scalar control methods were first widely used in IM speed control drives, followed by vector control methods, enabled by improvements in power electronic and microprocessor technology. In recent years, direct torque control (DTC) has been proposed to control IMs based on the principle of simultaneously controlling the stator flux and electromagnetic torque. In this paper, these three control methods for alternating current motor drives, which are the most widely used today, are compared to high-efficiency and standard IMs in experiments. © Sila Science.
Keywords: Direct torque control; High efficiency motor; Induction motor; Scalar control; Speed control; Vector control